Eksistentsi Pidana Mati Bagi Pelaku Korupsi Pada Saat Bencana - Latjeno, Muh Anugerah; Ikshan, Ahmad Yulianto; Isnawati, Muridah (Faculty of Law, University of Muhammadiyaha Surabaya, 2022)
Corruption has always been the pros and cons of imposing the death penalty, which can be imposed on perpetrators of budget corruption during disasters. The purpose of this study was to find out the existence of the death penalty for Corruption Perpetrators during the Covid-19 disaster. In addition, this study uses a normative juridical research method using a statutory approach and a case approach. The results of this study show that the Covid 19 outbreak that hit in 2020 yesterday was a non-natural disaster. Therefore, it is not uncommon to be a parameter in imposing the death penalty for perpetrators of budget corruption during a national natural disaster as in the Tipokor Law. The law mentions that the reason for the death penalty could be carried out under certain circumstances such as in a state of a national natural disaster. However, the Covid 19 outbreak is not a national natural disaster but a non-natural disaster other than that the amount of state losses is not clear. Hence, the existence of the threat of capital punishment is still very difficult to pass on to the perpetrators because the parameters that are the benchmark are not yet clear from the conditions in question.